Avaliação do potencial de nematóides entomopatogênicos para o controle da broca-da-bananeira Cosmopolites sordidus (Germar, 1824) - Bortoluzzi, Lilian (2009)
The black weevil (Cosmopolites sordidus) is the main pest of banana crops in several regions of the world, causing significant losses in productivity of the culture. The larvae build galleries in the rhizome or pseudostem base, affecting the development of the plant and the fruits, beside favoring the installation of pathogenic microrganisms. The use of nematodes to control of the pest can be an alternative, mainly because the insect's habits make them a potential target of entomopathogenic nematodes. So, this study had the objectives to evaluate isolates of entomopathogenic nematodes in laboratory conditions to their use in controlling the borer. Sixteen isolates Sterinernematidae and Heterorhabditidae were tested, applied on pseudostem (100JIs/cm2). The evaluation was performed 7 days after application. After, the most virulent isolates were compared with each other for production of nematodes in cadavers of wax moth (Galleria mellonella) and also about his compatibility with the insecticide carbofuran. All isolates were pathogenic to the adults of C. sordidus, except the isolate SC (Steinernema carpocapsae). The most virulent isolates were CB24 and CB40 (both of the Heterorhabditidae), which caused respectively 33,3% and 36,7% of mortality. The two isolates showed high production of JIs. The insecticide was compatible with isolated CB40 and incompatible with CB24, nevertheless, CB24 showed better performance in combination with carbofuran